(untitled) (Journal of the Management Sciences, 2026)
This study investigated the effect of financial performance of Deposit Money Banks (DMBs) on economic growth in Nigeria, with a specific focus on how key banking performance indicators influence GDP growth. The primary objective was to evaluate the short-run and long-run effects of Return on Assets (ROA), Return on Equity (ROE), and Capital Adequacy Ratio (CAR), on economic growth between 2000 and 2023. To achieve this, the study employed the Autoregressive Distributed Lag (ARDL) model, which accommodates variables integrated at different orders, ensuring robustness in the presence of both I(0) and I(1) series as confirmed by Augmented Dickey-Fuller (ADF) unit root tests. The bounds testing approach confirmed the presence of a long-run relationship among the variables (F-statistic = 6.182 > critical upper bound values). The ARDL estimation revealed that Return on Equity (ROE) has a statistically significant positive effect on GDP growth both in the short-run and long-run (short-run coefficient = 0.5004, p = 0.0179; long-run coefficient = 0.7705, p = 0.0004). In contrast, ROA and CAR did not exhibit significant short-run effects, although the second lag of CAR showed a delayed positive effect (p = 0.0419). Furthermore, the error correction term was significant and negative (-1.0665, p = 0.0001), indicating a strong speed of adjustment toward equilibrium. The study concluded that bank equity profitability is a crucial driver of Nigeria’s economic performance, while other indicators exhibit weaker direct effects. Based on the findings, it was therefore recommended that Nigerian banks prioritize reinvestment of equity earnings into growth-enhancing sectors and that regulators balance capital adequacy requirements with lending incentives. Besides, regulators should ensure that requirements do not stifle credit creation and that a balanced framework that encourages productive risk-taking be put in place.